Вплив факторів поверхні Землі на помилки у визначенні координат БПЛА пасивним содаром - Орлов, Д. І. (ХНУРЕ, 2024)
This work focuses on the analysis of factors influencing the accuracy of determining the coordinates of UAVs using passive acoustic methods. Model experiments were conducted for UAVs moving along a spiral trajectory, considering variables such as microphone array height and sound reflection coefficient. Statistical estimates of measurement errors were obtained, and two series of experiments were conducted to assess the impact of changing these variables. Results were approximated using cubic polynomials and linear regression, providing insights into the effectiveness of different models in analyzing the obtained data.
Keywords: визначення координат БПЛА; пасивний содар